Penerapan Model Discovery Learning dengan Penugasan Portofolio untuk Meningkatkan Kemampuan Argumentasi Siswa SMP: An Action Research Project in Implementing Discovery Learning Model with Portfolio Assignment to Improve Students’ Argumentation Competence for Junior High School Students in Indonesia - Yelli Riska Putri; Muhammad Rusdi; Syamsurizal Syamsurizal (Universitas Jambi, 2019)
Teaching and learning science in SMPN 9 Jambi Municipality, Indonesia do not encourage students to improve their argumentation competence. This research aims at investigating the implementation of discovery learning model with portfolio to improve the quality of students’ argumentation competence from both the teacher and students’ role. It investigates the learning environments that might be helpful for the implementation of discovery learning model with portfolio to improve the students’ argumentation skills. This research also investigate to what extent the discovery learning model with portfolio can improve students’ argumentation competence in learning science subjects. This research is a Classroom Action Research (CAR) which adopted Kemmis and Mc Taggart’s model consisting of planning, acting, observing, and reflecting. Participants involved in this research were the seventh graders of SMPN 9 Jambi Municipality (Class VII.H). This research employed observation sheets and documentation as the instruments of collecting the data. Findings of the research showed that discovery learning model with portfolio assignment can improve the students’ argumentation skills through its procedures and explanation of designing portfolio as learning media, and students’ argumentation skills as well as the learning environment which support the implementation of discovery learning with portfolio assignment. Safe, comfort, and meaningful learning environments can encourage students to learn actively which in turn can support their learning to improve the argumentation skills in learning science subject.